On the Dynamics of Rhyolite Dome Emplacement: Densities and Deformation Fields - Þorbjorg Ágústsdóttir 1981- (2009)
Silicic rocks in Iceland are generally associated with central volcanoes and are often emplaced on or around caldera rims. Rhyolite magma can rise, due to buoyancy forces and either form a cryptodome in the shallow crust or rise to the surface, where it erupts. Due to its high viscosity and resistance to flow it often accumulates and forms a lava dome over the vent. Some of these domes were formed subglacially while others were erupted under ice-free conditions. In this thesis some aspects pertaining to the dynamics of dome emplacement are studied, s.a. size and density of domes. A model to describe the deformation field above a rising cryptodome is proposed. A gravity survey was carried out in the area of Krafla in 2007 and 2008 to determine the mean bulk density values of rhyolite domes. Data on density and volumes is essential for meaningful modelling of the emplacement of cryptodomes and lava domes. Such data are scarce. Profiles were measured over three formations, ranging in size from Hlíðarfjall (310 m high and 2 km long), formed under ice 90 000 years BP, to Hrafntinnuhryggur (80 m high and 2.5 km long) formed 24 000 years BP under a glacier to Hraunbunga (125 m high and 1.8 km long) formed 10 000 years BP. The Holocene formation, Hraunbunga was measured as a reference to the subglacially formed ridges Hliðarfjall og Hrafntinnuhryggur on the Krafla caldera's rim. Mean bulk density for each formation was obtained by the Nettleton method. The results are that all the domes have low densities, reflecting both low grain-density and high porosity. The domes's density values are significantly smaller than those of the surroundings, creating a density contrast possibly sufficient to drive the ascent of rhyolite magma. Furthermore, results from gravity data demonstrate that these formations are neither buried by younger volcanic eruptives nor are any roots detected. The domes studied were therefore emplaced as vent-forming domes. No dome eruption has been observed with modern monitoring equipment in Iceland. The ...